2013
DOI: 10.1038/ncomms2591
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of memory consolidation during lapses in recall

Abstract: Memories that can be recalled several hours after learning may paradoxically become inaccessible for brief periods after their formation. This raises major questions about the function of these early memory lapses in the structure of memory consolidation. These questions are difficult to investigate because of the lack of information on the precise timing of lapses. However, the use of a single-trial conditioning paradigm in Lymnaea solves this problem. Here we use electrophysiological and behavioural experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 45 publications
(72 reference statements)
3
47
0
Order By: Relevance
“…Sporadic reports of temporary lapses in recall have been published in the last 4 decades regarding invertebrates and vertebrates (Gerber & Menzel, 2000;Marra, O'Shea, Benjamin, & Kemenes, 2013;Riege & Cherkin, 1971). By using a single-trial associative conditioning of feeding in Lymnaea, Marra and coworkers (2013) showed that lapses in recall during memory formation correspond to transitions between different phases of memory processing requiring distinct molecular pathways.…”
Section: Discussionmentioning
confidence: 96%
“…Sporadic reports of temporary lapses in recall have been published in the last 4 decades regarding invertebrates and vertebrates (Gerber & Menzel, 2000;Marra, O'Shea, Benjamin, & Kemenes, 2013;Riege & Cherkin, 1971). By using a single-trial associative conditioning of feeding in Lymnaea, Marra and coworkers (2013) showed that lapses in recall during memory formation correspond to transitions between different phases of memory processing requiring distinct molecular pathways.…”
Section: Discussionmentioning
confidence: 96%
“…Lymnaea stagnalis has been used widely for analysis of the cellular and molecular mechanisms of behaviour (Dyakonova et al, 2015;Koene, 2010;Marra et al, 2013;Pirger et al, 2014;Schmold and Syed, 2012), including studies at the single-cell level (Dyakonova et al, 2009(Dyakonova et al, , 2015Dyakonova and Dyakonova, 2010;Schmold and Syed, 2012). Therefore, our findings also reveal new opportunities for investigating the cellular basis of the intriguing interplay between motor and cognitive activities, which may have deep roots in evolution.…”
Section: Introductionmentioning
confidence: 94%
“…Lymnaea stagnalis snails have been used extensively for the analysis of cellular and molecular mechanisms of locomotion (Syed and Winlow, 1991b;Pavlova, 2010;Longley and Peterman, 2013), feeding (Benjamin and Rose, 1979;Elliott and Benjamin, 1989;Kemenes and Elliott, 1994;Staras et al, 1998Staras et al, , 2003Alania et al, 2004;Vehovszky et al, 2005;Vavoulis et al, 2007;Chistopolsky and Dyakonova, 2012), respiration (Syed and Winlow, 1991a,b;Tsyganov et al, 2004;Bell et al, 2007), learning and memory (Kemenes et al, 1997(Kemenes et al, , 2002Kojima et al, 1997;Spencer et al, 1999;Staras et al, 1998;Jones et al, 2003;Sangha et al, 2003;Kemenes et al, 2006;Nikitin et al, 2008;Marra et al, 2013;Mita et al, 2014;Naskar et al, 2014), and decision making (Pirger et al, 2014;Crossley et al, 2016). There are also approaches that have been developed only in this organism, particularly the studies at the single-cell level of freshly isolated, not cultured, neurons (Dyakonova et al, 2009(Dyakonova et al, , 2015Dyakonova and Dyakonova, 2010), and experimental tests of an extracellular chemical microenvironment that has been demonstrated to play a prominent 'socializing' role in adjusting single-cell physiology to the network state (Dyakonova et al, 2015).…”
Section: Risky Decision Making By Snails In a Vital Situationmentioning
confidence: 99%
“…Likewise, studies in the freshwater pond snail Lymnaea stagnalis have led to important insights into the mechanisms of memory formation, particularly for the modulation of memory (Kemenes et al, 2006; Marra et al, 2013; Lukowiak et al, 2014). Moreover, these invertebrates have been pivotal in the initial recognition of non-synaptic forms of neuronal plasticity and their possible role in the neuronal representation of memory (Mozzachiodi and Byrne, 2010; Nikitin et al, 2013).…”
Section: Invertebrates In Neurobiology Researchmentioning
confidence: 99%